New Evidences on the Process Sensitivity of Some Renewable Blends Based on Starch considering Their Melt Rheological Properties. (21st February 2016) - Dimonie, Doina; Petrache, Marius; Damian, Celina; Anton, Liliana; Musat, Miruna; Dima, Ştefan-Ovidiu; Jinescu, Cosmin; Maria, Rapa
Abstract : The degradability and processability of new renewable materials based on starch and PVOH were studied using the melt flow index (MFI) method by measuring the melt rheological properties which depend not only on the extrusion conditions and material formulation but also on the macromolecule characteristics which can be modified by chemical degradation. These results were correlated with other material properties like color and cross-linking degree. The obtained results show that flowing in the melted state of the studied materials is accompanied by a second process of chains chemical degradation. It was observed that, at the same level of additivation, under identical extrusion conditions, the melted blends with corn starch as main component are highly mechanically sensitive and degrade mostly by chains scission and those with PVOH as major component are highly temperature sensitive and degrade mainly by cross-linking. The obtained results show also that each PVOH-starch blend requires particular formulation and individual windows of melt processing conditions. These results are a good proof that the MFI method is a good path to study the degradability and moldability of process sensitive polymeric materials like those based on starch and PVOH.